Study of hydrogen adsorption onto kenaf sorbent surface by metal impregnation method - Ezaty, S. N. (2020)
The potential of kenaf (Hibiscus cannabinus L.) as hydrogen materials was investigated. Kenaf core from National Kenaf and Tobacco Board (NKTB), Kelantan, Malaysia have been synthesized and characterized to achieve the improvement on kenaf's surface support, and then evaluated the hydrogen adsorption performance of the modified nickel-kenaf adsorbent (MK-Ni). Kenaf core have been transformed in particulate forms (size: 500 mm) for high performance adsorbents and impregnated into chemicals of Nickel Nitrate, Ni(NO3)2 in different concentrations. To improve the hydrogen adsorption, the surface was tailored using Formaldehyde (HCHO) and Potassium Hydroxide (KOH) before the process of metal impregnation. The modified kenaf and raw kenaf surface morphological structure were characterized by Variable-Pressure Scanning Electron Microscope (VPSEM) and the elements in kenaf sample was analyzed by using Energy Dispersive X-ray (EDX) spectroscopy. The hydrogen adsorption is compared with laboratory scale of hydrogen adsorption system by ultra-purity hydrogen gas (H2) in ambient temperature. Two cyclic operation for delivery performance of hydrogen shows that modified nickel-kenaf with 0.4 M concentration in 4 bar pressure bed had better improvement in hydrogen adsorption performance.